2007
DOI: 10.1002/hlca.200790027
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Methyl Diazoacetate with (E)‐ and (Z)‐1,2‐Bis(trifluoromethyl)ethene‐1,2‐dicarbonitrile: Novel and Unanticipated Pathways

Abstract: Dedicated to Mordecai Rubin, Technion, Haifa, on the occasion of his 80th birthdayThe cycloadditions of methyl diazoacetate to 2,3-bis(trifluoromethyl)fumaronitrile ((E)-BTE) and 2,3-bis(trifluoromethyl)maleonitrile ((Z)-BTE) furnish the 4,5-dihydro-1H-pyrazoles 13. The retention of dipolarophile configuration proceeds for (E)-BTE with > 99.93% and for (Z)-BTE with > 99.8% (CDCl 3 , 258), suggesting concertedness. Base catalysis (1,4-diazabicyclo[2.2.2]octane (DABCO), proton sponge) converts the cycloadducts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In the dihydro-1H-pyrazole from methyl diazoacetate and (E)-BTE, J trans,vic ¼ 0 was found [1]. Van der Waals strain in the persubstituted cyclopentenes 9 probably distorts the regular half-chair conformation, i.e., substantial values of J trans,vic were observed (Fig.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…In the dihydro-1H-pyrazole from methyl diazoacetate and (E)-BTE, J trans,vic ¼ 0 was found [1]. Van der Waals strain in the persubstituted cyclopentenes 9 probably distorts the regular half-chair conformation, i.e., substantial values of J trans,vic were observed (Fig.…”
mentioning
confidence: 93%
“…They beautifully serve as stereochemical probes in mechanistic investigations. It has recently been demonstrated that the 1,3-dipolar cycloadditions of methyl diazoacetate (1) to (E)-and (Z)-BTE proceed with retention of dipolarophile configuration (> 99.93% and > 99.8%, resp.) [1].…”
mentioning
confidence: 98%
See 2 more Smart Citations